Minat Beli Ulang Produk Starbucks Ditinjau dari Cita Rasa dan Persepsi Harga: Survei pada Konsumen Starbucks di Kota Tasikmalaya - Muhammad Gunawan; Rita Tri Yusnita; Suci Putri Lestari (CV. Ulil Albab Corp, 2022)
This research was conducted with the aim of knowing the effect of Taste and Price Perception on the intention to repurchase Starbucks products. The method used in this study is a survey method using data obtained directly through questionnaires distributed to 100 respondents who are Starbucks Tasikmalaya consumers. The technique used in this research is multiple linear regression analysis. Based on the results of the study, it can be seen that Taste and Price Perception simultaneously have a significant effect on Repurchase Interest, Taste partially has a significant effect on Repurchase Intention, and Price Perception partially has a significant effect on Repurchase Interest of Starbucks products.